Development of E-Modules for Employee Training based on Interactive Media Performance Management Materials at PT. DMA - Among Waluyo; Zainal Abidin Arief; Rudi Hartono (Indonesian Journal of Pedagogy and Teacher Education, 2025)
This research aims to develop an interactive media-based training e-module to enhance employee performance management at PT. DMA is a company operating in the oil palm plantation industry. The primary challenge lies in the competency gaps among supervisors and managerial staff, negatively impacting leadership, innovation, and productivity. Traditional training methods have proven ineffective in addressing these issues. Therefore, this study proposes the use of interactive media-based e-modules to offer a more adaptive, participatory, and technology-driven learning experience. The research adopts the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed e-module underwent expert validation and was rated highly: media experts (92%), instructional design experts (91%), material experts (87%), teacher users (92%), small group testing (87%), and large group testing (86%). These findings indicate that the e-module is feasible for employee training activities at PT. DMA. Effectiveness was further supported by data showing an increase in average test scores from 51 (pre-test) to 87 (post-test). The N-Gain test produced a score of 0.7, categorized as “effective.” In conclusion, the use of interactive media-based e-modules in performance management training is effective in improving learning outcomes and has strong potential to support employee development at PT. DMA.